Height‐based equations as screening tools for high blood pressure in pediatric practice, the GENOBOX study. Issue 6 (21st May 2022) - Pérez‐Gimeno, Gloria; Ruperez, Azahara I.; Gil‐Campos, Mercedes; Aguilera, Concepción M.; Anguita, Augusto; Vázquez‐Cobela, Rocío; Skapino, Estela; Moreno, Luis A.; Leis, Rosaura; Bueno‐Lozano, Gloria
Abstract: Due to the absence of easily applicable cut‐off points to determine high blood pressure or hypertension in children, as in the adult population, blood pressure is rarely measured in the pediatrician's clinical routine. This has led to an underdiagnosis of high blood pressure or hypertension in children. For this reason, the present study evaluate the utility of five equations for the screening of high blood pressure in children: blood pressure to height ratio, modified blood pressure to height ratio, new modified blood pressure to height ratio, new simple formula and height‐based equations. The authors evaluated 1599 children between 5 and 18 years. The performance of the five equations was analyzed using the receiver‐operating characteristics curves for identifying blood pressure above P90th according to the American Academy of Pediatrics Clinical Practice Guideline 2017. All equations showed an area under the curve above 0.882. The new modified blood pressure to height ratio revealed a high sensitivity whereas the height‐based equations showed the best performance, with a positive predictive value above 88.2%. Finally, all equations showed higher positive predictive values in children with overweight or obesity. The height‐based equation obtained the highest PPV values above 71.1% in children with normal weight and above 90.2% in children with overweight or obesity. In conclusions, the authors recommend the use of the height‐based equations equation because it showed the best positive predictive values to identify children with elevated blood pressure, independently of their sex, pubertal and weight status.